Candida tropicalis antifungal cross-resistance is related to different azole target (Erg11p) modifications (2013)
ABSTARCT: Candida tropicalis ranks between third and fourth among Candida species most commonly isolated from clinical specimens. Invasive candidiasis and candidemia are treated with amphotericin B or echinocandins as first-line therapy, with extended-spectrum triazoles as acceptable alternatives. Candida tropicalis is usually susceptible to all antifungal agents, although several azole drug-resistant clinical isolates are being reported. However, C. tropicalis resistant to amphotericin B is uncommon, and only a few strains have reliably demonstrated a high level of resistance to this agent. The resistance mechanisms operating in C. tropicalis strains isolated from clinical samples showing resistance to azole drugs alone or with amphotericin B cross-resistance were elucidated. Antifungal drug resistance was related to mutations of the azole target (Erg11p) with or without alterations of the ergosterol biosynthesis pathway. The antifungal drug resistance shown in vitro correlated very well with the results obtained in vivo using the model host Galleria mellonella. Using this panel of strains, the G. mellonella model system was validated as a simple, nonmammalian minihost model that can be used to study in vitro-in vivo correlation of antifungals in C. tropicalis. The development in C. tropicalis of antifungal drug resistance with different mechanisms during antifungal treatment has potential clinical impact and deserves specific prospective studies.